Elevated Levels of Neutrophil Activated Proteins, Alpha-Defensins (DEFA1), Calprotectin (S100A8/A9) and Myeloperoxidase (MPO) Are Associated With Disease Severity in COVID-19 Patients - Shrivastava, Shubham; Chelluboina, Shweta; Jedge, Prashant; Doke, Purwa; Palkar, Sonali; Mishra, Akhilesh Chandra; Arankalle, Vidya A. (Frontiers in Cellular and Infection Microbiology, 2021)
Understanding of the basis for severity and fatal outcome of SARS-CoV-2 infection is of paramount importance for developing therapeutic options and identification of prognostic markers. So far, accumulation of neutrophils and increased levels of pro-inflammatory cytokines are associated with disease severity in COVID-19 patients. In this study, we aimed to compare circulatory levels of neutrophil secretory proteins, alpha-defensins (DEFA1), calprotectin (S100A8/A9), and myeloperoxidase (MPO) in COVID-19 patients with different clinical presentations. We studied 19 healthy subjects, 63 COVID-19 patients with mild (n=32) and severe (n=31) disease, 23 asymptomatic individuals identified through contact tracing programme and 23 recovering patients (1-4 months post-disease). At the time of disease presentation, serum levels of DEFA1 were significantly higher in patients with mild (mean230 ± 17, p<0.0001) and severe (mean452 ± 46, p<0.0001) disease respectively in comparison to healthy subjects (mean113 ± 11). S100A8/A9 proteins were significantly higher in COVID-19 patients (p<0.0001) irrespective of disease severity. The levels of DEFA1, S100A8/A9 and MPO reduced to normal in recovering patients and comparable to healthy subjects. Surprisingly, DEFA1 levels were higher in severe than mild patients in first week of onset of disease (p=0.004). Odds-ratio analysis showed that DEFA1 could act as potential biomarker in predicting disease severity (OR=11.34). In addition, levels of DEFA1 and S100A8/A9 were significantly higher in patients with fatal outcome (p=0.004 and p=0.03) respectively. The rise in DEFA1 levels was independent of secondary infections. In conclusion, our data suggest that induction of elevated levels of alpha-defensins and S100A8/A9 is associated with poor disease outcome in COVID-19 patients.